2009
DOI: 10.1021/jo8026142
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Formation of Nitriles and Alkoxy Radicals from N-Alkoxybenziminoyl Chlorides in Solution

Abstract: A series of N-alkoxybenziminoyl chlorides were synthesized and reacted with tributyltin hydride in the presence of AIBN to generate the corresponding N-alkoxybenziminoyl radicals. This methodology successfully generates the desired radicals, which undergo a rapid and highly efficient β-scission reaction, as shown by the formation of the corresponding nitriles and products derived from alkoxy radicals. The intermediate N-alkoxybenziminoyl radical could not be trapped by employing high concentrations of Bu3SnH o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…When the reaction was done with chloranil (CA) as the sensitizer at 350 nm (entry 2), the only reactivity observed was E / Z isomerization (as confirmed by the same reaction without CA present). Previously, we have observed that reactions of oximes and oxime ethers derived from aldehydes react slower than those derived from ketones. Our next step, therefore, was to look at the reactivity of the corresponding acetophenone oxime ether ( 2 ). Reacting oxime ether 2 with DCA at 420 nm (entry 4) did not result in any significant product formation; again, degradation of the starting material was the main pathway.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When the reaction was done with chloranil (CA) as the sensitizer at 350 nm (entry 2), the only reactivity observed was E / Z isomerization (as confirmed by the same reaction without CA present). Previously, we have observed that reactions of oximes and oxime ethers derived from aldehydes react slower than those derived from ketones. Our next step, therefore, was to look at the reactivity of the corresponding acetophenone oxime ether ( 2 ). Reacting oxime ether 2 with DCA at 420 nm (entry 4) did not result in any significant product formation; again, degradation of the starting material was the main pathway.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To promote formation of the iminoxyl radicals, the reactions were carried out with chloranil (CA) as the sensitizer. The CA radical anion is known to be basic, and spectroscopic studies have shown the formation of the semiquinone radical via proton transfer from an oxime radical cation to the CA radical anion . Irradiation of oxime 3 at 350 nm in the presence of CA (Table , entry 7) resulted in the formation of new signals in the NMR spectrum.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 The nitriles were proposed to result from intermediate imidoyl radicals, which are formed via hydrogen atom abstraction at the iminyl carbon (Scheme 1). 7 …”
Section: Introductionmentioning
confidence: 99%